2018
DOI: 10.1111/jphd.12268
|View full text |Cite
|
Sign up to set email alerts
|

Community water fluoridation online: an analysis of the digital media ecosystem

Abstract: The dominant neutral sentiment of the network may signify that anti- and pro-sides of the debate are viewed as balanced, not just in number but also in quality of information. Despite high inlinks to pro-sources, anti-fluoridation sentiment maintains influence online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Thus the current research adds to the growing literature examining the ideological antecedents of rejection of science (Hornsey & Fielding, 2017; Lewandowsky & Oberauer, 2016), situating these predictors within the larger theoretical framework of the Dual Process Model (Duckitt & Sibley, 2009). Our results also extend previous research by examining beliefs about community water fluoridation and evolution, two issues which are subject to continued public debate (Barnes et al, 2017; Helmi et al, 2018) and, in the case of water fluoridation, can have wide ranging impacts on public health (Armfield, 2007; Moore et al, 2017).…”
Section: Studysupporting
confidence: 83%
“…Thus the current research adds to the growing literature examining the ideological antecedents of rejection of science (Hornsey & Fielding, 2017; Lewandowsky & Oberauer, 2016), situating these predictors within the larger theoretical framework of the Dual Process Model (Duckitt & Sibley, 2009). Our results also extend previous research by examining beliefs about community water fluoridation and evolution, two issues which are subject to continued public debate (Barnes et al, 2017; Helmi et al, 2018) and, in the case of water fluoridation, can have wide ranging impacts on public health (Armfield, 2007; Moore et al, 2017).…”
Section: Studysupporting
confidence: 83%
“…Critics of fluoridation and vaccination have well established portals on the World Wide Web [e.g. Helmi, Spinella and Seymour, 2018]. The key here is that social media facilitate the expression of many voices.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of social media has created an opportunity for researchers to use these tools as sources of data on a range of topics, including on the spread of illnesses and attitudes to health-related topics [2-4]. A few studies have also used social media to examine public opinion on dental health, especially fluoridation [5,6]. However, prior research has suggested that social media may be used to spread distorted or false information and that such information may have important negative consequences, for instance, when dangerous information is spread about how to contain epidemics or when mental disorders are associated with negative emotions and unsupportive tweets [7,8].…”
Section: Introductionmentioning
confidence: 99%